2016
DOI: 10.1155/2016/7897351
|View full text |Cite
|
Sign up to set email alerts
|

Geohelminth Infections and Nutritional Status of Preschool Aged Children in a Periurban Settlement ofOgun State

Abstract: This study assessed the geohelminth and nutritional status of preschoolers in a periurban community of Ogun state. Fresh stool specimens were collected for laboratory analysis, processed using ether concentration method, and examined under the microscope for geohelminth ova. Demographic characteristics and daily nutrient intake of children were subjectively assessed during an interview session with parents, following anthropometric data collection. Data obtained were analysed using a statistical software for W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
2
10
1
1
Order By: Relevance
“…Individual-level factors like not wearing shoes was significantly associated with STH infection. In a study conducted in Peru, playing with soil, not wearing sandals, and picking food from the ground were common habits found among PSAC infected with STH [42]. Also, not using improved water source for drinking was significantly associated with STH infection.…”
Section: Discussionmentioning
confidence: 99%
“…Individual-level factors like not wearing shoes was significantly associated with STH infection. In a study conducted in Peru, playing with soil, not wearing sandals, and picking food from the ground were common habits found among PSAC infected with STH [42]. Also, not using improved water source for drinking was significantly associated with STH infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, children wearing protective shoes often remove it when playing on soil because they mostly have one and need to make the shoe last longer; thereby getting exposed to active penetration of infective hookworm larvae when playing in contaminated soil in their environment [ 25 ]. Inadequate use of footwears is a risk factor in the transmission of hookworm infections [ 19 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric data of height, recumbent length (children < 2 years) and weight were obtained as described [ 19 , 21 ]. Urine samples were examined for micro-haematuria and S. haematobium ova using reagent strip and sedimentation method [ 20 ].…”
Section: Main Textmentioning
confidence: 99%
“…However, recent reviews of the impact of treatment by Cochrane and the Campbell collaboration have reported only weak evidence for weight gain and none on height gain after treatment [9,10]. The effect on preschool children has been less extensively studied, but several papers have suggested some association [11].…”
Section: Introductionmentioning
confidence: 99%